2012
DOI: 10.1055/s-0032-1311590
|View full text |Cite
|
Sign up to set email alerts
|

Urine and Serum Concentrations of Inhaled and Oral Terbutaline

Abstract: We examined urine and serum concentrations after therapeutic use of single and repetitive doses of inhaled and supratherapeutic oral use of terbutaline. We compared the concentrations in 10 asthmatics and 10 healthy subjects in an open-label, cross-over study with 2 mg inhaled and 10 mg oral terbutaline on 2 study days. Further, 10 healthy subjects were administrated 1 mg inhaled terbutaline in 4 repetive doses with total 4 mg. Blood samples were collected at baseline and during 6 h after the first inhalations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 4 publications
7
51
4
Order By: Relevance
“…Mean ± SEM administration. Noteworthy, the systemic concentrations observed were 4 times higher than that observed by Elers et al (2012a) after oral administration of 10 mg terbutaline with reported peak systemic concentrations of only 6.2 ± 4.8 ng ml −1 (median ± interquartile range). Likewise, we observed several indications of systemic effects of inhaled terbutaline, including elevated V O 2 at rest and during submaximal exercise at 80 % of V O 2max , along with lowered systemic concentrations of K + and elevated concentrations of glucose and lactate.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Mean ± SEM administration. Noteworthy, the systemic concentrations observed were 4 times higher than that observed by Elers et al (2012a) after oral administration of 10 mg terbutaline with reported peak systemic concentrations of only 6.2 ± 4.8 ng ml −1 (median ± interquartile range). Likewise, we observed several indications of systemic effects of inhaled terbutaline, including elevated V O 2 at rest and during submaximal exercise at 80 % of V O 2max , along with lowered systemic concentrations of K + and elevated concentrations of glucose and lactate.…”
Section: Discussionmentioning
confidence: 58%
“…Active substance (Terbutaline, Bricanyl Turbohaler 0.5 mg) was delivered by the Pharmacy of RegionH, Copenhagen, Denmark. Inhaled terbutaline has been shown to be quickly absorbed, reaching peak systemic concentrations (C max ) 30 min (T max ) following administration (Elers et al 2012a). The onset of action of inhaled terbutaline is within a few minutes with a duration of action of up to 6 h (datasheet, Bricanyl ® Turbohaler, AstraZeneca).…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, blood samples were collected in vacutainers with clot activator and spun at 3,000 rpm for 15 min, after which serum samples were collected and stored at Ϫ80°C. Serum TER was analyzed by liquid chromatography-tandem mass spectrometry as previously described (11) and performed by the World Anti-Doping Agency-accredited Norwegian Doping Control Laboratory at Oslo University Hospital, in Oslo, Norway.…”
Section: Methodsmentioning
confidence: 99%